Study on the Influence of Particle Size and Grade of Total Tailings on the Fluidity of High-Concentration Filling Slurry considering Strength. (4th May 2021) - Duan, Xiaobo; Huang, Yucheng; Zheng, Wenxiang
Abstract : To find out the effect of total tailing particle size and grading on the rheological property of filling slurry with high concentration, especially in high intensity, the experiment on the particle size of total tailings was conducted firstly to get the corresponding result. Then, the collapse test of mixed slurry with different cement tailing ratios and different concentrations was carried out to get the corresponding slump value and extension value. Furthermore, the rotational viscometer was applied to test shear stress in the samples with different cement tailing ratios and different concentrations, from which the relevant rheological parameter can be achieved through the Bingham rheological model. Finally, a strength test to mixed slurry block with different cement tailing ratios and different concentrations was conducted (3 days, 7 days, and 28 days); the corresponding intensity values were taken. The experiment result illustrates that with the increase of concentration and cement tailing ratio of the slurry, the collapse degree and extended degree of slurry decreased, while yield stress, plastic viscosity, and strength increased. When the concentration was raised from 70% to 72%, all parameters that characterize good fluidity reduced obviously. As a result, the mixed slurry with a concentration of 70% and cement tailing ratio of 1 : 8 not only meets the requirements of production intensity but also has good mobility and low pipeline wear.